Tetraploid Wheat Landraces in the Mediterranean Basin: Taxonomy, Evolution and Genetic Diversity - Oliveira, Hugo R. (Public Library of Science, 2012)
The geographic distribution of genetic diversity and the population structure of tetraploid wheat landraces in the Mediterranean basin has received relatively little attention. This is complicated by the lack of consensus concerning the taxonomy of tetraploid wheats and by unresolved questions regarding the domestication and spread of naked wheats. These knowledge gaps hinder crop diversity conservation efforts and plant breeding programmes. We investigated genetic diversity and population structure in tetraploid wheats (wild emmer, emmer, rivet and durum) using nuclear and chloroplast simple sequence repeats, functional variations and insertion site-based polymorphisms. Emmer and wild emmer constitute a genetically distinct population from durum and rivet, the latter seeming to share a common gene pool. Our population structure and genetic diversity data suggest a dynamic history of introduction and extinction of genotypes in the Mediterranean fields.